2001
DOI: 10.1097/00005537-200111000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Bolus Transit and Airway Protection Coordination in Older Dysphagic Patients

Abstract: Pharyngeal transit of the bolus may be prolonged in elderly individuals. Swallowing coordination mechanisms appear to be intact in the majority of elderly patients with dysphagia, but gestures may be weak and ineffective. Early laryngeal elevation may be an effective strategy to avoid aspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
35
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 8 publications
5
35
1
3
Order By: Relevance
“…While decreases in swallow durations have been considered desirable for overall functionality and swallow safety, researchers have recently revised their notion on swallow durations and now consider that faster swallowing is not necessarily more functional or safe. 18,21,32 Rather, it may be reasonable to propose that there exists a minimum time requirement for coordination of airway protection and bolus propulsion and flow through the oropharynx and laryngopharynx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While decreases in swallow durations have been considered desirable for overall functionality and swallow safety, researchers have recently revised their notion on swallow durations and now consider that faster swallowing is not necessarily more functional or safe. 18,21,32 Rather, it may be reasonable to propose that there exists a minimum time requirement for coordination of airway protection and bolus propulsion and flow through the oropharynx and laryngopharynx.…”
Section: Discussionmentioning
confidence: 99%
“…15 Decreased elevation and excursion of the hyolaryngeal complex is considered one cause of penetration and aspiration. [18][19][20][21] Submental muscle contraction elevates the hyolaryngeal complex. EMST treatment produces significantly longer durations, higher peak amplitudes, and greater average amplitudes of the submental muscles' EMG signal when compared to dry and wet swallows.…”
mentioning
confidence: 99%
“…Previous investigations did not find loss on swallowing efficiency before 80 years, in the swallow index risk (19) and in esophageal contraction amplitude (8,20) . Bolus pharyngeal transit time in older subjects is longer with swallows of 20 mL volume of liquid bolus, but not with swallows of 1 mL bolus volume (15) , compared with younger subjects. Swallows of a non viscous bolus (water) cause an increase in the duration of pharyngeal transit and pharyngeal clearance in subjects older than 55 years (2) .…”
Section: Introductionmentioning
confidence: 73%
“…Most of the studies which evaluated the pharyngeal transit in the elderly showed that the transit is longer than in younger subjects (12,13,15,19,24) . Increased slowness in movement is a general characteristic in aging (16) ; however, these investigations had the participation of older subjects than we included in this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation